Economic Security, Private Investment, and Growth in Developing Countries - Poirson, Helene (IMF Working Papers; Working Paper ;, 1998)
This paper provides empirical support for the view that enhanced economic security fosters private investment and growth in developing countries. An analysis for 53 developing countries suggests that most aspects of economic security have improved since the mid-1980s; that private investment is mostly influenced by the risk of expropriation, the degree of civil liberty, and the degree of independence of the bureaucracy; and that economic growth is affected by the risk of expropriation and political terrorism in the short run, and by corruption and contract repudiation in the long run.